الإبداعات المغربية باللغات الأجنبية بين سلطة اللغة وسلطة الهوية: قراءة تراتبية: The Moroccan Writings in Foreign Languages Between Linguistic Authority and Identity-based Authority: A Hierarchical Reading - بوعلي فؤاد (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2015)
أثارت الكتابة الإبداعية باللغات الأجنبية العديد من المواقف المتعارضة في الحقلين: الأكاديمي، والثقافي. فقد عرف تاريخ المغرب الحديث سجالاً قوياً بخصوص هوية الكتابات الإبداعية باللغات الأجنبية، بين مَن يرى فيها استلاباً ثقافياً، ومَن يرفض ربط الجنسية الأدبية بالانتماء اللغوي، بل وربطها بالمتخيّل الجماعي أكثر من أيّ شيء آخر، ثمّ بالمنتوج الأدبي بوصفه تجسيداً لهذا المتخيّل. فالتعبير عن الذات بلغة أجنبية يطرح للنقاش مفاهيم، مثل: الهوية الثقافية، والسلطة، والخصوصية، والعلاقة بالآخر. وباستخدام القراءة التراتبية التي ظهرت في الدراسات بعد الكولونيالية أمكننا إثبات التلازم بين استعمال اللغة الفرنسية في الإبداع ومسار الفرنكفونية بوصفها إيديولوجيا استعماريةً تفرض لغتها على الشعوب والفضاءات الذيلية. The debate over literary writing in a foreign language has instigated a lot of dichotomous points of view in Moroccan academic and cultural circles. History of modern Morocco has witnessed strong ongoing debates about the identity of creative writings in foreign language. There are those who would consider such writings as cultural alienation. Contrary to that, there are those who refuse to link literary text to language belonging, and link it instead to the collective imaginary and to the literary product as a manifestation of this imaginary. In fact, expressing the self by using a foreign language puts into question notions such as cultural identity, authority, nation-building, and otherness. By applying the theory of hierarchical reading which appeared in the post colonial studies, we have established the relationship between using French in creative writings and La Francophonie as a colonial ideology imposed on people and annexed spaces.